Chronotypes and Scheduling Needs of Nurses Operating in University-Affliated Hospitals - Pipatkulchai, Daranee; Pituksung, Auengporn; Chimchalong, Ratree; Namthep, Janthana (Journal of Thailand Nursing and Midwifery Council, 2021)
Objective: To examine university-affliated hospital nurses’ chronotypes and corresponding shift-scheduling needs Design: Descriptive study Methodology: The sample consisted of 831 nurses having served in the nursing divisions of university-affliated hospitals for a minimum of one year and assigned to at least one afternoon or night shift per month. Data were collected using a questionnaire distributed and retrieved via Google Form. The questionnaire consisted of three parts: 1) the demographic data form; 2) the scheduling needs survey; and 3) the Thai version of the Morningness-Eveningness Questionnaire (T-MEQ). The data was analysed using descriptive statistics and a chi-square test. Results: The majority of the nurses (64.7%) exhibited the intermediate chronotype, which correlated significantly to the need to be assigned to work sessions that overlapped night shifts, 10-hour-per-day work, assignment to one shift type, work experience, types of patients under care, marital status, and personal responsibilities (p < 0.05). Concerning scheduling needs, slightly over half of the nurses (51.4%) preferred the morning shift, about three-fourths (73.9%) preferred sessions overlapping the morning shift, and nearly all (93.5%) wished they could choose when to have holidays. Also, a huge majority of the nurses (90.5%) wanted to avoid being rotated or seconded to a different division, whilst nearly two-thirds (65.8%) wanted to avoid being assigned to only one shift type. Work experience, types of patients under care, marital status, and personal responsibilities correlated significantly to shift-scheduling needs and assignment to one shift type (p < 0.05). Recommendations: It is recommended that hospital administrators and ward managers survey the nurses’ chronotypes and scheduling needs, offer them opportunities to choose the shift types, and make shift scheduling more ﬂexible.